Language attitudes of primary school teachers in Vitoria-Gasteiz. Issue 2 (2nd April 2020) - Becker, Misha
ABSTRACT: Vitoria-Gasteiz, the capital city of the bilingual Basque Autonomous Community of Spain, is a largely Spanish-speaking city: over 90% of the city's population claims Spanish as their native language and less than one-fifth of the city's adult population is bilingual in Basque and Spanish (compare with more than one-third of the population of San Sebastián). Nevertheless, enrollment in Basque immersion (Model D) schools has grown over the last three decades and continues to grow. As of the 2018–2019 school year, 80% of primary and secondary public school students in the Basque Autonomous Community were enrolled in Model D schools. The goal of this study was to investigate the linguistic attitudes of primary school teachers in different school models in Vitoria-Gasteiz for the purpose of identifying factors in the positive growth of Basque as a minority language, as well as current challenges for growth, in this sociolinguistically adverse environment. Results are then related to opportunities and challenges for other minoritized languages undergoing language revitalization.